2019
DOI: 10.1037/xhp0000621
|View full text |Cite
|
Sign up to set email alerts
|

Transposed letter priming effects and allographic variation in Arabic: Insights from lexical decision and the same–different task.

Abstract: Reading is resilient to distortion of letter order within a word. This is evidenced in the “transposed-letter (TL) priming effect,” the finding that a prime generated by transposing adjacent letters in a word (e.g., jugde) facilitates recognition of the base word (e.g., JUDGE), more than a “substituted-letter” control prime in which the transposed letters are replaced by unrelated letters (e.g., junpe -JUDGE). The TL priming effect is well documented for European languages that are written using the Roman alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 55 publications
(154 reference statements)
10
29
2
Order By: Relevance
“…In this study, transposed-letter primes, as in the prime–target pair ئٮتنايٮن (/i tn ajin/)—ئٮنتايٮن (/i nt ajin/, very ; transposed letters are underlined), produced as much priming as identity primes (e.g., ئٮنتايٮن /intajin/, very —ئٮنتايٮن /intajin/, very ), but only when the transposed letters were in the same graphemic chunk and retained their allographic form (as in the example above). Boudelaa and colleagues (2019) obtained similar results in Arabic with a set of experiments using masked priming in a same–different match task. In this study, transposed letter primes produced robust facilitation for both word and nonword targets.…”
Section: Letter Connectedness and Reading Difficulty In Arabicsupporting
confidence: 69%
See 3 more Smart Citations
“…In this study, transposed-letter primes, as in the prime–target pair ئٮتنايٮن (/i tn ajin/)—ئٮنتايٮن (/i nt ajin/, very ; transposed letters are underlined), produced as much priming as identity primes (e.g., ئٮنتايٮن /intajin/, very —ئٮنتايٮن /intajin/, very ), but only when the transposed letters were in the same graphemic chunk and retained their allographic form (as in the example above). Boudelaa and colleagues (2019) obtained similar results in Arabic with a set of experiments using masked priming in a same–different match task. In this study, transposed letter primes produced robust facilitation for both word and nonword targets.…”
Section: Letter Connectedness and Reading Difficulty In Arabicsupporting
confidence: 69%
“…Several previous studies have indicated that Arabic does not show reliable masked form priming effects—that is, facilitated processing of targets when they share letter sequences with primes (Frost et al, 2005; Perea et al, 2010; but see Perea et al, 2014). These results, along with comparable findings from Hebrew, have been interpreted as evidence that the lexicon in Semitic languages is organised primarily based on morphological information, rather than on orthographic form (see, for example, Boudelaa et al, 2019; Frost et al, 1997, 2005; Velan & Frost, 2009, 2011). More recent research, however, has found reliable masked form priming effects in Arabic with task adjustments that reduce lexical processing demands (Perea et al, 2014).…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Another important aspect of Arabic words is that they constitute a remarkably dense lexical ‘space’ wherein letter transpositions within tri‐ or quadriliteral roots often results in other known roots (e.g., بعيد /bʕeed/, meaning far , becomes عبيد /ʕbeed/, meaning slaves ). Boudelaa et al (2019) estimated that this happens about 54% of the time for the commonly used Arabic roots, compared to only 7% of the time for English three‐letter words. Not surprisingly, numerous studies in Arabic and Hebrew have shown that facilitation from root‐preserving primes or parafoveal previews (e.g., the preview تقسيمات for the target الأقسام, both containing the root قسم /qsm/) is eliminated if root‐letter order is not preserved (e.g., if the parafoveal preview is either الأسقام or الأمساق where root letter transposition created the root سقم /sqm/ or the pseudo root مسق /msq/, respectively, for the target of الأقسام; Hermena, Juma, & AlJassmi, in preparation; see also Perea, Abu Mallouh, & Carreiras, 2010; Velan & Frost, 2007, 2009, 2011 for similar results in other tasks in both Arabic and Hebrew).…”
Section: The Arabic Language and Writing Systemmentioning
confidence: 99%